Formation of a model for the use of industrial enterprises resources as part of the production and logistics chain - O. E. Astafyeva (Вестник университета)
The article defines the ways of using the resources of an industrial enterprise as a result of the transformation of business processes occurring in the context of interactions within the ecosystem. The approaches to the use of resources aimed at ensuring the resource potential and determining the chains of creating “value” in the resource model, the development of which was carried out in the blocks “production” – “Logistics” – “Interaction” – “Infrastructure”, have been analysed. It has been proposed to identify resources according to the parameters of the value of use, complementarity, the possibility of substitution and the benefits received from the use by economic entities as a result of ecosystem interaction. An assessment of the resource requirements has been presented, taking into account the level of automation of operations in business processes that make up the economic benefits of use and utility.